MECHANIZM TRANSAKCJI PAPIERAMI WARTOŚCIOWYMI NA RYNKU REGULOWANYM - Bielecka-Dobroczek, Aleksandra (Zeszyty Prawnicze, 2017)
The Mechanism of Securities’ Transactions on the Regulated Market Summary The article presents the variety of categories of securities and financial instruments in public trading, especially rich after the recent legal changes. The author attempts to analyze the mechanisms of securities’ transfer and transactions in public trading (stock exchange transactions) and their realization stressing their specific features. All contracts are built according to a certain standard, concluded through specialized broker agent on the different, they depend on the construction of the transferred instruments regulated market. Their performance is practically carried out by a clearing corporation (National Depository for Securities) using the procedure of multilateral compensation (netting). Mechanisms of securities’ transfer are different, they depend on the construction of the transferred instruments.